A Galois-Grothendieck-type correspondence for groupoid actions - Paques, A.; Tamusiunas, T. (Algebra and Discrete Mathematics, 2014)
In this paper we present a Galois-Grothendiecktype correspondence for groupoid actions. As an application a Galois-type correspondence is also given.